2017
DOI: 10.1080/13880209.2017.1299768
|View full text |Cite
|
Sign up to set email alerts
|

Folic acid ameliorates celecoxib cardiotoxicity in a doxorubicin heart failure rat model

Abstract: Context: The cardiotoxic effect of selective cyclo-oxygenase-2 inhibitors is well known. While rofecoxib and valdecoxib have been withdrawn, celecoxib remains on the market. Folic acid, a naturally occurring vitamin, has been shown to reduce myocardial ischemia and post-reperfusion injury in rats.Objective: This study examined the cardiac effects of celecoxib and folic acid on doxorubicin-induced cardiomyopathy in rats. Materials and methods: Cardiomyopathy was induced in male Wistar rats with six intraperiton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 50 publications
0
19
0
1
Order By: Relevance
“…Recent studies often research models that use DOX 6 times every other day at 2.5 mg/kg ( Merlet et al, 2013 ; Lončar-Turukalo et al, 2015 ; Cappetta et al, 2017a ; Ahmad et al, 2017 ; Cappetta et al, 2017b ; Elhadidy et al, 2020 ). Histological examination showed that this injection protocol results in irregularly spaced myocardial fibers with inflammation, edema, and leukocyte cell infiltration.…”
Section: Anthracycline Cardiomyopathy Modelsmentioning
confidence: 99%
“…Recent studies often research models that use DOX 6 times every other day at 2.5 mg/kg ( Merlet et al, 2013 ; Lončar-Turukalo et al, 2015 ; Cappetta et al, 2017a ; Ahmad et al, 2017 ; Cappetta et al, 2017b ; Elhadidy et al, 2020 ). Histological examination showed that this injection protocol results in irregularly spaced myocardial fibers with inflammation, edema, and leukocyte cell infiltration.…”
Section: Anthracycline Cardiomyopathy Modelsmentioning
confidence: 99%
“…CVb3 infection of mouse hearts is routinely detected by the activities of biochemical markers, virus expression levels and histological changes on the heart on day 8 pi. Ck and Ldh are the most commonly used biochemical markers (ghormade et al, 2014;Ahmad et al, 2017). in this study, mice were inoculated with CVb3 to induce myocarditis, and then received nCC by oral gavage daily.…”
Section: Discussionmentioning
confidence: 99%
“…The HF injury model in vivo was generated as previously reported (21). After 12 weeks, rats were administered with 6 equal intraperitoneal injections of 2.5 mg/kg doxorubicin (DOX; Fresenius Kabi Oncology Ltd.) over a period of 2 weeks.…”
Section: Reverse Transcription-quantitative Polymerase Chain Reaction (Rt-qpcr)mentioning
confidence: 99%